Funcionalização de celulose bacteriana com peptídeo RGD para reparação tecidual de pele - Lopes, Rute [UNESP] (2015)
Bacterial cellulose (BC) exhibits a broad diversity of applications. The aim of this study was to develop a scaffold or temporary dressing for skin tissue repair, whereof the BC would be functionalized with an RGD peptide. The synthesized materials were physicochemically characterized and submitted to in vitro analyses to assess their capacity of stimulating fibroblasts adhesion, proliferation and immune response. The developed materials would be applied in skin tissue repair that may be hampered by a series of sistemic factors, such as diabetes, smoking and nutritional deficiency. In theses cases, the usage of biomaterials as a drug delivery system or wound dressing, aiding or accelerating the repair and healing processes, becomes a necessity. The RGD peptide sequence (Arginine-Glycine-Aspartic Acid) is found in many extracellular matrix (ECM) proteins, and it is frequently used to promote cell adhesion, mediated by integrins, in biomaterials. The synthesized peptide sequence was chosen by means of computational analysis. Two types of membrane were synthesized, the BC-RGDAds in which the RGD peptide was adsorbed, and the BC-RGDImz in which the peptide was covalently bonded to the membrane, therefore, immobilized. These materials, together with the pure BC membrane, were characterized by contact angle analysis, x-ray diffractometry (XRD), scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FT-IR), thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC). Subsequently, the samples were submitted to in vitro assays of cellular viability and cellular morphology, using the fibroblast lineage L929; moreover, to evaluate the immune and inflammatory response, the nitric oxide production assay as well as TNF-α and IFN-γ cytokines determination assays were performed using Balb/c mice cells. The results indicate that the BC-RGDAds and the BC-RGDImz membranes...